Personalized Nutrition Intervention Improves Health Status in Overweight/Obese Chinese Adults: A Randomized Controlled Trial - Kan, Juntao; Ni, Jiayi; Xue, Kun; Wang, Feijie; Zheng, Jianheng; Cheng, Junrui; Wu, Peiying; Runyon, Matthew K.; Guo, Hongwei; Du, Jun (Frontiers in Nutrition, 2022)
Background: Overweight and obesity increase the risk of noncommunicable diseases (NCDs). Personalized nutrition (PN) approaches may provide tailored nutritional advice/service by focusing on individual’s unique characteristics to prevent against NCDs. Objective: We aimed to compare the effect of PN intervention with the traditional “one size fits all” intervention on health status in overweight/obese Chinese adults. Methods: In this 12-week randomized controlled trial, 400 adults with BMI ≥ 24 kg/m2 were randomized to control group (CG, n=200) and PN group (PNG, n=200). The CG received conventional health guidance according to the Dietary Guidelines for Chinese Residents and Chinese DRIs Handbook, whereas the PNG experienced PN intervention that was developed by using decision trees based on the subjects’ anthropometric measurements, blood samples (phenotype), buccal cells (genotype), and dietary and physical activity (PA) assessments (baseline and updated). Results: Compared with the conventional intervention, PN intervention significantly improved clinical outcomes of anthropometric (e.g., body mass index (BMI), body fat percentage, waist circumference) and blood biomarkers (e.g., blood lipids, uric acid, homocysteine). The improvement in clinical outcomes was achieved through behavior change in diet and PA. The subjects in the PNG had higher China dietary guidelines index values and PA levels. Personalized recommendations of “lose weight”, “increase fiber” and “take multivitamin/mineral supplements” were the major contributors to the decrease of BMI and improvement of lipid profile. Conclusion: We provided the first evidence that PN intervention was more beneficial than conventional nutrition intervention to improve health status in overweight/obese Chinese adults. This study provides a model of framework for developing personalized advice in Chinese population. Trial registration: Chictr.org.cn (ChiCTR1900026226).